Updating Understanding of Macular Microvascular Abnormalities and Their Correlations With the Characteristics and Progression of Macular Edema or Exudation in Coats' Disease - Zhang, Juan; Ruan, Lu; Jiang, Chen; Yang, Qian; Ju, Yuqiao; Chang, Qing; Huang, Xin (Frontiers in Medicine, 2022)
Objective To investigate the associations of macular microvascular abnormalities with the characteristics and progression of macular edema or exudation in Coats' disease, toward an updated understanding of possible risk factors for macular edema or exudation. Methods Twenty-six eyes (26 patients) with Coats' disease and macular edema or exudation underwent multimodal imaging and were followed for 18 months. The eyes were classified according to their outcomes (refractory or improved). Macular capillary affections were assessed by optical coherence tomography angiography (OCTA) and fluorescein angiography (FA). Histopathological analysis of the macular region of an additional enucleated eye was performed. Results OCTA revealed telangiectasia in the deep capillary plexus (DCP) in 76.9% and the superficial capillary plexus (SCP) in 34.6% of 26 eyes with macular edema or exudation of Coats' disease, exceeding the rate detected by FA (21.4%). Eyes with intraretinal cystoid spaces/exudates of the macula presented higher presence of telangiectasia in the SCP (57.1% with vs. 8.3% without, X2 = 6.801, P = 0.009) and DCP (92.9 with vs. 58.3% without, X2 = 4.338, P = 0.037). The parafoveal vessel densities (VDs) and fractal dimension in the SCP and DCP were lower in affected eyes than in contralateral eyes (all P < 0.001). The VD in SCP (P = 0.009) and DCP (P = 0.010) were lower in refractory group than in improved group. Dilated capillaries with incomplete vessel walls and adjacent inflammatory cells were detected in the neuroretina of the macula in histopathological specimen. Conclusions Macular capillary abnormalities, including telangiectasia and VD loss, were positively detected in eyes with macular edema or exudation of Coats' disease. Intraretinal cystoid spaces/exudates of the macula, rather than subretinal exudates, may be related to macular telangiectasia. VD losses in the SCP and DCP may be risk factors for refractory macular edema or exudation.